Development of Acmeological Competence in Rising Social Teachers - Yessenamanova, Karlygash; Arinova, Bakyt; Zhambylkyzy, Marina; Rakhimbayeva, Roza; Zhunussova, Dinara (Frontiers in Education, 2022)
In the modern educational process, it is important to constantly develop the personality studied in the context of acmeology. The relevance of this study is determined by the issue of the development of acmeological competence in rising social educators. The purpose of the study was to study the level of development of acmeological competence and its components in students. The methodology is based on the experimental method presented by the student survey. Fisher’s exact test, Chi-squared distribution, Student’s t-test were also used in the study. This study was conducted at Al-Farabi Kazakh National University and Abay Kazakh National Pedagogical University. The sample consisted of 253 students. The results show that 22.13% of first-year respondents had low motivation, 52.96% – medium, 24.90% – high; in the fourth-year, the level of motivation changed: 10.67% of respondents had low motivation, 46.25% – medium, 43.08% – high. The average level of motivation was 15.10 ± 2.37 and 17.00 ± 1.96 among the first- and fourth-year students, respectively, and had a tendency to increase. Thus, its average values grew toward the completion of studies. It was found that 3.56% of first-year respondents were too cautious, 51.38% were moderately cautious, and 48.62% were inclined to take risks; in the context of the fourth-year students, these indicators were 2.37, 69.96, and 30.04%, respectively. Research has shown that with age, knowledge, and experience, the willingness to take risks decreases. When conducting a correlation analysis, it was found that there is an average positive correlation between the level of motivation and the level of propensity to take risks. The results of this work indicate the need for further scientific research on the issue of acmeological competence not only of social teachers, but also of other educators in order to achieve heights in personal development and improve the learning process. In the future, it is planned to study the types of motivation and methods of its increase (self-motivation, affirmation, visualization).